Peningkatan Pengetahuan Pengelolaan Keuangan Rumah Tangga dan Investasi Melalui Pelatihan Bagi Ibu - Ibu PKK di Kantor Kelurahan Kamal, Jakarta Barat - Suripto, H.; Susanti, Ika; Maharani, Virda Rosita; Khoirunnasikin, Khoirunnasikin; Mizan, Erik Takhir (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2024)
The purpose of conducting this activity is Community Service Program (PKM) . With Title: "Improving Knowledge of Household Financial Management and Investment for PKK Mothers at the Office of Kelurahan Kamal, West Jakarta." The general objective of this community service activity is to train PKK mothers in Kelurahan Kamal to enhance their knowledge of the importance of managing finances more effectively. Additionally, another goal is to instill understanding gradually to avoid dependence on lending institutions. The project also aims to make mothers more productive, not solely relying on their husbands' salaries but also assisting their husbands in various ways such as staying up late or selling goods needed by friends or neighbors. The methods applied in this project involve lectures and discussions on financial management, including planning through recording every need and expenditure. Participants are also provided with basic knowledge of investments, including gold savings, savings/deposits, and other investment options. The conclusion of this community service activity is that housewives increasingly realize the importance of managing finances and making sound investment choices, saving, and possessing skills in prioritizing needs.